2011
DOI: 10.1093/jnci/djq508
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Measurement in Randomized Clinical Trials in Breast Cancer: An Updated Systematic Review (2001–2009)

Abstract: Reporting of QOL methodology could be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 238 publications
2
63
0
8
Order By: Relevance
“…Desde la década 1970-79 existen múltiples estudios y revisiones que describen la CV en CaM 11,12 . Actualmente, los estudios se centran en las poblaciones más vulnerables o en pacientes sobrevivientes, con más de 5 años de sobrevida 15,18,19 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Desde la década 1970-79 existen múltiples estudios y revisiones que describen la CV en CaM 11,12 . Actualmente, los estudios se centran en las poblaciones más vulnerables o en pacientes sobrevivientes, con más de 5 años de sobrevida 15,18,19 .…”
Section: Discussionunclassified
“…También permite detectar grupos de mayor riesgo o vulnerabilidad, favoreciendo un abordaje interdisciplinario desde la etapa diagnóstica con intervenciones preventivas. Finalmente, la CV puede utilizarse con fines pronósticos que se correlaciona con la sobrevida [7][8][9][10][11][12] . Las variables que afectan la CV pueden ser de tipo psicosocial o físicas.…”
unclassified
“…The implementation of proper radiotherapy in the treatment of breast cancer can significantly prolong survival time in patients [31]. In one study, high Cu / Zn ratios following radiotherapy was found to be potentially useful in assessing possible improvements in breast cancer patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development in diagnostic screening and anticancer treatment has helped breast cancer patients survive/live longer, for whom treatment-related problems can have a Hui-Yan Niu 1 , Chun-Ying Niu 2 , Jia-He Wang 1 , Yi Zhang 1 , Ping He 1 * major impact on their HRQL. Therefore, there has been a lot of interest in conducting HRQL studies among women with breast cancer (Goodwinet al, 2003;Montazeri, 2008;Lemieux et al, 2011).…”
Section: Introductionmentioning
confidence: 99%